Outcomes of aortic valve surgery for rheumatic heart disease in Indigenous Australians: a 27-year longitudinal study - Rohen Skiba; Tim Soon Cheok; D.-Yin Lin; Craig Morrison; Gareth Crouch; Stewart R. Anderson; Gregory Rice; Jayme Bennetts (The Cardiothoracic Surgeon)
Abstract Background In Australia, acute rheumatic fever occurs almost exclusively in young Indigenous peoples, with young- to middle-aged Indigenous people being predominantly affected by rheumatic heart disease. This can result in a need for aortic valve surgery. Despite the increasing use of bioprosthetic valves in younger Indigenous Australians with rheumatic heart disease, there is limited long-term data comparing survival and reoperation rates between valve types or repair strategies in this high-risk population. This is a single-centre database analysis of 27 years of consecutive rheumatic heart disease aortic valve surgery and long-term results. Primary outcomes were all-cause mortality and all-cause revision surgery, as a time from index (primary) aortic valvular surgery, whether it be replacement or repair. Results Two-hundred sixty-eight patients underwent aortic valve surgery for rheumatic heart disease. Average age at time of index surgery was 50.1 years. Sixteen (6.0%) underwent revision. Time to death (mortality recorded in 93 (34.7%)) was 6.1 ± 4.3 years. There was no difference in risk of mortality between primary replacement or repair (HR = 1.12; p = 0.87). In the replacement population, there was no survival difference between bioprosthetic or mechanical valve (HR = 1.42; p = 0.11). Time to revision surgery was 7.9 ± 4.4 years. Aortic valve repair as primary surgery was associated with an increased risk of revision (sub-distribution hazard ratio (SHR) 8.22; p = 0.01). When replacement was performed, there was a significantly greater risk of revision for bioprosthetic valves, as opposed to mechanical valves (SHR 3.26; p = 0.045). Conclusions The rheumatic heart disease population in Australia is young at time of index surgery, and there is no survival benefit to replacement or repair. Replacement should have an appropriately chosen bioprosthetic or mechanical valve replacement, with an increased risk of revision for bioprosthetic valves which is in keeping with existing literature. Primary aortic valve repair for rheumatic heart disease is associated with long-term increased risk of revision surgery.